Food as an allergen in the etiology of bronchial asthma of children in Turkey - Göğüş, S.; Saraçlar, Y.; Özkaragöz, K. (The Turkish Journal of Pediatrics, 1969)
In this study the role of food allergy in respiratory allergy in children at the Hacettepe Faculty of Medicine Allergy Clinic is investigated. Compared with pollen, mold spores and other inhalants, food allergens are a minor factor. Of 105 cases studied, only two showed bronchospasms due to foods, and these two also proved to be allergic to many other allergens. Six cases of urticaria, two of colic and four of rhinitis were also considered to be food allergies.The role of foods as allergens, and the types of allergic reactions in different age groups are summarized. Though foods play little part in the production of bronchospasms, they should be considered in the evaluation of bronchial asthma, especially in patients who present year-round symptoms, and are not given relief from hyposensitization treatment.As claimed by many allergists, skin tests with antigens were shown to be unreliable in confirming food allergy, and provocation tests seem to be the only feasible methods so far for routine exploration of asthmatic children.